Korelasi Karbon Monoksida dan Derajat Rokok dengan Fungsi Paru pada Pengemudi Ojek Online - Khairani, Rita; Putri, Mustika Anggiane; Setyaningrum, Dyah Ayu Woro (Jurnal Biomedika dan Kesehatan, 2023)
Background Cigarette smoke is the main source of exposure to carbon monoxide (CO) besides air pollution. When cigarette smoke is inhaled, carbon monoxide is absorbed through the lungs, enters the bloodstream, and then binds to hemoglobin to form carboxyhemoglobin (COHb), whose levels in the blood can be measured as a marker of cigarette smoke absorption. Both smoking habits and CO levels can affect lung function, after smoking, blood CO levels will increase and lung function will decrease significantly. Methods This study used an analytic observational method with a cross-sectional design with a total sample of 99 respondents. Data collection in September-December 2022 using the Brinkman Index questionnaire, Fagerstrom Test for Nicotine Dependence (FTND) questionnaire, exhaled CO levels, and spirometry examination. Results 47.5% exhaled CO levels on 0-6 ppm or in a green zone, 77.8% of subjects smoked, 57.6% FTND score was 0-2, 51.5% of subjects had restricted lung function, and 79.5% subjects with obstruction. Exhaled CO levels were strongly correlated with the Brinkman index (r=0.654, p=0.000), and moderately significant correlation with the FTND score (r=0.544, p=0.000). There is no correlation between exhaled CO levels and degree of smoking with lung function. Conclusions Exhaled CO levels have a significant correlation with smoking and nicotine dependence but do not correlate with pulmonary function test.